Analysis of Formation and Implementation of Health Promotion Programs at Dr. Moewardi Hospital Surakarta - Kusumawardani, Dyah Ayu; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2024)
Background: Health promotion needs to be given in hospitals even though the hospital is engaged in curative and rehabilitative fields. The area of preventive and curative that differentiates is the target. The preventive sector targets healthy people, while the curative sector targets patients and their families and health care workers. Health promotion in hospitals also seeks to prevent the patient's family from getting the same disease as what happened to the patient. The purpose of this study is to analyze the formation and implementation of health promotion programs at Dr. Moewardi Regional Public Hospital Surakarta. Subjects and Method: Qualitative study using in-depth interviews. Interviews were conducted at the regional general hospital Dr. Moewardi, Surakarta, Indonesia in January to March 2023. Interviews were conducted with 2 main informants who were PKRS committee secretaries who were the Head of Public Relations and Marketing Head, 6 regular informants, and 4 additional informants who were randomly selected and were the targets of PKRS activities. The variables in this study are input, process, and output. The data is processed through the stages of data reduction, data presentation, and drawing conclusions and source triangulation. Results: Hospital Health Promotion activities already have job descriptions and are carried out according to SOPs. The process in this study before the activity started was always planned, when the activity started, the team was involved but there was no supervision by the Hospital Health Promotion Committee and evaluations were always held. The output of this study is that the Hospital Health Promotion activities carried out are in accordance with the letter of assignment formed and are in accordance with the SOP and this is a reference for Hospital Health Promotion activities in the future.. Conclusion: The findings from this study are that Hospital Health Promotion at Dr. Moewardi Regional Public Hospital has been going well and is routinely carried out, but the human resources involved for Hospital Health Promotion activities are still lacking even though everything is in accordance with the operational plan formed. Keywords: analysis, health promotion, system theory Correspondence: Dyah Ayu Kusumawardani. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email:dyahayuksma96@gmail.com. Mobile: +6281466847498